2004
DOI: 10.1259/bjr/30116822
|View full text |Cite
|
Sign up to set email alerts
|

Computer-based detection and prompting of mammographic abnormalities

Abstract: Mammographic film reading is a highly demanding task, particularly in screening programmes where the reader must perform a detailed visual search of a large number of images for early signs of abnormality, which are often subtle or small, and which occur very infrequently. False negative cases, where signs of abnormality are missed by a film reader, are known to occur. Computer based algorithms can be used to detect abnormal patterns in images, but it is not possible to reliably detect all signs of abnormality… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(18 citation statements)
references
References 24 publications
0
17
0
1
Order By: Relevance
“…Other imaging techniques, such as ultrasonography and magnetic resonance imaging, have also been used in breast cancer screening. Unfortunately, even with the inclusion of these imaging techniques, about 20% of breast cancer patients still cannot be detected [5]. Plasma (or serum) biomarkers (such as antigens and protein patterns) are promising [6,7]; however, they are still far from clinical use.…”
Section: Introductionmentioning
confidence: 99%
“…Other imaging techniques, such as ultrasonography and magnetic resonance imaging, have also been used in breast cancer screening. Unfortunately, even with the inclusion of these imaging techniques, about 20% of breast cancer patients still cannot be detected [5]. Plasma (or serum) biomarkers (such as antigens and protein patterns) are promising [6,7]; however, they are still far from clinical use.…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, up to 20 % of new breast cancer incidents are not detected by this X-ray method, and for younger women with a genetic predisposition, sensitivity is not more than 40 %. Furthermore, specificity of the method is relatively low since only one out of three lesions is found to be malignant (Astley 2004; Benson et al 2004; Roder et al 2008). As a result, mammography screening may lead to overdiagnosis (Brennan et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, there has been a great deal of research in development of computerized methods for automatic and accurate detection of MC clusters, which could potentially assist radiologists in diagnosis of breast cancer. A recent review of various MC detection methods reported in the literature can be found, for example, in [2]–[4]. …”
Section: Introductionmentioning
confidence: 99%